Agrarian vision, industrial vision, and rent-seeking: A viewpoint - Johanna Jauernig; Ingo Pies; Paul B. Thompson; Vladislav Valentinov (Journal of Agricultural and Environmental Ethics, 2020)
Many public debates about the societal significance and impact of agriculture are usefully framed by Paul Thompson's distinction between the “agrarian” and the “industrial vision.” The key argument of the present paper is that the ongoing debate between these visions goes beyond academic philosophy and has direct effects on the political economy of agriculture by influencing the scope of rent-seeking activities that are undertaken primarily in the name of the agrarian vision. The existence of rent-seeking activities is shown to reflect the fact that the agrarian vision is not universally supported, which is certainly true of the industrial vision as well. The key argument of the present paper is that these two philosophical visions of agriculture are not radically incongruent. Rather, they share a common ground within which they are even mutually supportive. If agricultural policy making is oriented toward this common ground, it may reduce overall dissatisfaction with the resulting institutional regime of agricultural production. Such an agricultural policy may also stimulate the emergence of new business practices that not only enable efficient agricultural production but also minimize negative ecological impact and preserve cultural landscapes.
Keywords: 330; agrarian vision; CSR; rent-seeking; business ethics